2015
DOI: 10.1002/ps.4031
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the respiratory chain inhibitor ametoctradin to the mitochondrialbc1complex

Abstract: The binding mode of ametoctradin differs from other agricultural fungicides such as cyazofamid and the strobilurins. This explains the lack of cross-resistance with strobilurins and related inhibitors, where resistance is mainly caused by G143A amino acid exchange. Accordingly, mixtures or alternating applications of these fungicides and ametoctradin can help to minimise the risk of the emergence of new resistant isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…These two populations were excluded from the subsequent analyses of AOX‐related resistance because a target site resistance to amisulbrom could not be completely ruled out. All the other resistant to amisulbrom populations were sensitive in the presence of SHAM, which showed that the resistance mechanism involved AOX‐related resistance, presumably AOX overexpression . The percentage of populations displaying the AOX‐related resistance mechanism varied from year to year, ranging from 4% in 2012 to 54% in 2017.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These two populations were excluded from the subsequent analyses of AOX‐related resistance because a target site resistance to amisulbrom could not be completely ruled out. All the other resistant to amisulbrom populations were sensitive in the presence of SHAM, which showed that the resistance mechanism involved AOX‐related resistance, presumably AOX overexpression . The percentage of populations displaying the AOX‐related resistance mechanism varied from year to year, ranging from 4% in 2012 to 54% in 2017.…”
Section: Resultsmentioning
confidence: 91%
“…In P. viticola , the role of AOX overexpression in resistance to QoIs has been established. A fitness study performed in vitro without selection pressure and with a combination of sporangia with and without AOX overexpression showed a strong reduction in AOX expression in sporangia after several multiplication cycles . The competitiveness of sporangia with AOX overexpression but without selection pressure seems to be weaker.…”
Section: Discussionmentioning
confidence: 99%
“…QoI fungicides interact with one of these sites in such a way that a single mutation (Gly143Ala) causes resistance, whereas the recently introduced fungicide Ametoctradin (QoSI; FRAC code 45) binds to the second site, and does not show cross resistance with QoIs (Fehr et al 2015). Currently Ametoctradin is only registered for use against oomycete pathogens, but there seems no reason why this important target site could not be exploited to widen the disease control spectrum.…”
Section: Finding New Modes Of Actionmentioning
confidence: 99%
“…The cytochrome bc 1 complex (respiratory complex III, Cyt bc 1 , EC: http://1.10.2.2) of eukaryotic mitochondrial and prokaryotic energy‐transducing membranes is a proven target for antimicrobial agents of medical and agricultural interest [1–7]. This enzyme, which is widespread in nature, functions as a protonmotive ubiquinol:cytochrome c oxidoreductase, conserving and converting the Gibbs energy obtained from the exergonic oxidation of ubiquinol by cytochrome c into a transmembrane proton gradient which may be harnessed for other endergonic processes, typically ATP synthesis by an F o F 1 ATP synthase [8,9].…”
Section: Introduction and General Enzymatic Mechanism Of The Cytochromentioning
confidence: 99%